Network pharmacology and experimental analysis to reveal the mechanism of Dan-Shen-Yin against endothelial to mesenchymal transition in atherosclerosis - Hong, Mengyun; Wu, Yubiao; Zhang, Haiyi; Gu, Jinchao; Chen, Juanjuan; Guan, Yancheng; Qin, Xiude; Li, Yu; Cao, Jiahui (Frontiers in Pharmacology, 2022)
Atherosclerosis is the chronic inflammatory disease characterized by the formation of plaque and endothelial dysfunction. Upon the proinflammatory conditions, endothelial cells adopt a mesenchymal phenotype by a process called endothelial to mesenchymal transition (EndMT) which plays an important role in the pathogenesis of atherosclerosis. Dan-shen-yin (DSY) is a famous formula of Traditional Chinese Medicine used in the treatment of cardiovascular disease. However, the molecular mechanism of DSY for treating atherosclerosis remains unknown. Therefore, network pharmacology-based strategy was used in this study to predict therapeutic targets of DSY, and further in vitro experiments was applied to understand the pharmacological molecular mechanism. The targets of the corresponding ingredients in DSY, EndMT and atherosclerosis were obtained and further were used to construct the PPI network followed by network topology and function enrichment analysis. Network pharmacology analysis revealed that PI3K/AKT pathway was the principle signaling pathway of DSY against EndMT in atherosclerosis. Molecular docking simulation indicated the strong binding ability of bioactive ingredients toward the PI3K/AKT pathway molecules. Experimentally, DSY could efficiently modify expression of EndMT signature genes and decreased expression of PI3K/AKT pathway signals including integrinαV, integrinβ1, PI3K, AKT1 in TGF-β2 treated HUVEC. LASP1, uprestream of PI3K/AKT pathway, was found to exert strong binding affinities with the majority of bioactive ingredients, and was induced by EndMT promoting stimuli involving IL-1β, TGF-β2, and hypoxia, and can be highly decreased by DSY. Knock-down of LASP1 attenuated the expression of Integrin αV, integrin β1, PI3K, AKT1 and EndMT related genes induced by TGF-β2, and minimized the effect of DSY. Our study thus shows that DSY potentially exerts anti-EndMT activity through LASP1/PI3K/AKT pathway, and provides a possible new therapeutic intervention for atherosclerosis.